COMPETENCY NEEDED IN E-RECRUITMENT IN EAST JAVA :CONTENT ANALYSIS - Rita Mutiarni; Dygtania Sandra Ovilia (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
The purpose of this study is that with this assumption, researchers are interested in analyzing the competencies needed by companies for prospective employees in the Marketing Admin field, which are published on job vacancies sites on social media. This research is expected to provide benefits for job seekers with the aim of exploring the competencies needed by the company in the Marketing Admin section. The data used uses secondary data, with units of analysis and observations taken from social media telegram Loker Jatim in 2022. The data analysis technique uses content analysis. The results show that the competencies needed to become a marketing admin are undergraduate education, employee communicative skills and can master Microsoft Office programs, self-concept and values ​​of prospective employees must have an honest, friendly and agile attitude, personal characteristics of prospective employees with male type - male and female and for the maximum age limit at a maximum age of 30 years and the motive of prospective company employees must have 1-2 years of work experience and prospective applicants in the marketing admin field must require that prospective employees must have challenges and targets and be able to work under pressure.